Cux2 activity defines a subpopulation of perinatal neurogenic progenitors in the hippocampus. Issue 2 (3rd October 2014) - Yamada, Makiko; Clark, Jessica; McClelland, Christine; Capaldo, Emily; Ray, Ayush; Iulianella, Angelo
ABSTRACT The hippocampus arises from the medial region of the subventricular (SVZ) within the telencephalon. It is one of two regions in the postnatal brain that harbors neural progenitors (NPs) capable of giving rise to new neurons. Neurogenesis in the hippocampus is restricted to the subgranular zone (SGZ) of the dentate gyrus (DG) where it contributes to the generation of granule cell layer (gcl) neurons. It is thought that SGZ progenitors are heterogeneous, differing in their morphology, expression profiles, and developmental potential, however it is currently unknown whether they display differences in their developmental origins and cell fate‐restriction in the DG. Here we demonstrate that Cux2 is a marker for SGZ progenitors and nascent granule cell neurons in the perinatal brain. Cux2 was expressed in the presumptive hippocampal forming region of the embryonic forebrain from E14.5 onwards. At fetal stages, Cux2 was expressed in early‐forming Prox1+ granule cell neurons as well as the SVZ of the DG germinal matrix. In the postnatal brain, Cux2 was expressed in several types of progenitors in the SGZ of the DG, including Nestin/Sox2 double‐positive radial glia, Sox2+ cells that lacked a radial glial process, DCX+ neuroblasts, and Calretinin‐expressing nascent neurons. Another domain characterized by a low level of Cux2 expression emerged in Calbindin+ neurons of the developing DG blades. We used Cux2‐Cre mice in genetic fate‐mapping studies and showed almost exclusive labeling of Calbindin‐positive gcl neurons, but not in any progenitor cell types or astroglia. This suggests that Cux2+ progenitors directly differentiate into gcl neurons and do not self‐renew. Interestingly, developmental profiling of cell fate revealed an outside‐in formation of gcl neurons in the DG, likely reflecting the activity of Cux2 in the germinative matrices during DG formation and maturation. However, DG morphogenesis proceeded largely normally in hypomorphic Cux2 mutants lacking Cux2 expression. Taken together we conclude that Cux2 expression reflects hippocampal neurogenesis and identifies non‐self‐renewing NPs in the SGZ. © 2014 The Authors Hippocampus Published by Wiley Periodicals, Inc.